System for measuring and monitoring radiation exposure - SUH, JUN SUHK; PARK, HYEUN SUK (2024)
본 발명은 방사선 측정 관리시스템에 관한 것으로, 피검자에 조사되는 방사선량을 검출하는 방사선 검출센서(1), 상기 방사선 검출센서(1)에서 검출된 방사선량에 대한 미약한 센서 신호를 증폭하는 증폭기(11), 검출된 방사선량에 대응된 전기적인 구형파 신호로 변환하는 신호변환기(12), 상기 신호변환기(12)로 부터 입력된 신호로 부터 피검자의 X선 피폭량으로 산출하고 피검자의 방사선 피폭량 측정 데이터를 블루투스 통신을 통하여 스마트기기(2)로 전송하는 제어부(13)를 포함하는 방사선 측정기기와, 상기 방사선 측정기기에서 블루투스로 전송받는 스마트기기(2), 및 상기 스마트기기(2)로 부터 전송된 방사선 측정 데이타를 보관 및 열람하도록 하고 개인별 누적된 방사선량이 미리 설정된 기준치에 근접하는 경우에 당국에 조치를 취하도록 정보를 제공하는 관리자 서버(3)를 포함하여 구성됨으로써, 개개인의 각종 검진을 위해 다양한 곳에서 방사선을 조사한 경우에도 관리자 서버에 저장된 누적 방사선 피폭량 데이타에 근거하여 미리 설정된 기준치에 근접하거나 초과하는 경우에 방사선 조사에 의한 검진을 제한하도록 함으로써 방사선의 과도한 피폭에 따른 질병 발생을 방지하도록 효율적인 조치를 취할 수 있게 된다. The present invention relates to a radiation measurement management system, wherein the system is configured by including: a radiation measurement device including a radiation detection sensor (1) for detecting a radiation amount emitted to a subject, an amplifier (11) for amplifying a weak sensor signal of the radiation amount detected by the radiation detection sensor (1), a signal converter (12) for performing conversion to an electrical square wave signal corresponding to the detected radiation amount, and a control part (13) for calculating an exposure amount of an X-ray for the subject from a signal input from the signal converter (12) and transmitting radiation exposure amount measurement data of the subject to a smart device (2) through Bluetooth communication; the smart device (2) for reception from the radiation measurement device through Bluetooth; and a manager server (3) for storing and allowing access to radiation measurement data transmitted from the smart device (2) and providing information to a corresponding authority to take action if an accumulated radiation amount for each individual approaches a preconfigured reference value, so that even when radiation is administered at various locations for individual medical examinations, efficient measurement can be carried out to prevent a disease caused by excessive radiation exposure by limiting examinations using radiation when accumulated radiation exposure amount data stored in the manager server approaches or exceeds a preconfigured reference value.